2021
DOI: 10.1021/acsomega.1c02591
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Fingolimod Derivatives as Antibacterial Agents

Abstract: We recently identified fingolimod as a potent antibiofilm compound by screening FDA-approved drugs. To study if the antibacterial activity of fingolimod could be further improved and to explore in-depth structure−activity relationships, we synthesized 28 novel fingolimod derivatives and evaluated their efficacy against Staphylococcus aureus grown in planktonic/single cell and biofilms. The most effective derivatives were tested on preformed S. aureus biofilms and against Gram-negative bacteria Acinetobacter ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Inhibiting QS is an interesting alternative approach to reduce the drug use in infections involving biofilms, as preventing biofilm formation maintains bacteria in a more susceptible planktonic state. The QS inhibitory activity of fingolimod and its derivatives has been previously demonstrated by our group ( Gilbert-Girard et al, 2020b ; Zore et al, 2021 ). To investigate whether etrasimod could also act as quorum sensing inhibitor (QSI), we tested it using a previously described C. violaceum platform ( Skogman et al, 2016 ).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Inhibiting QS is an interesting alternative approach to reduce the drug use in infections involving biofilms, as preventing biofilm formation maintains bacteria in a more susceptible planktonic state. The QS inhibitory activity of fingolimod and its derivatives has been previously demonstrated by our group ( Gilbert-Girard et al, 2020b ; Zore et al, 2021 ). To investigate whether etrasimod could also act as quorum sensing inhibitor (QSI), we tested it using a previously described C. violaceum platform ( Skogman et al, 2016 ).…”
Section: Resultsmentioning
confidence: 56%
“…In a previous study, we found that fingolimod, an FDA-approved drug for the treatment of relapsing-remitting multiple sclerosis, has antibacterial and anti-biofilm activity against Staphylococcus aureus ( Gilbert-Girard et al, 2020b ). Medicinal chemistry efforts by our group provided further insights on structure-activity relationships and yielded several fingolimod derivatives with more potent antibacterial activity ( Zore et al, 2021 ). Fingolimod is a structural analogue of sphingosine, a sphingoid base naturally found in mammalian cells, which has a well reported antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a burgeoning interest in identifying synergistic adjuvants for colistin to solve the problem of MDR bacteria ( Kim and Eom, 2021 ). Although FLD exhibits potent antibacterial activity on Gram-positive bacteria, its bactericidal activity on Gram-negative bacteria was not strong ( Zore et al, 2021 ). FLD as an antibiotic adjuvant was rarely studied to enhance the efficacy of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, new strategies are necessary both for the management of antibiotics and for the development of new antibacterial agents with fewer side effects . Among the natural sources, animal and vegetal extracts, metabolites of microbial origin, e.g., defense enzymes, and organic acids, and secondary metabolites from plants, such as phytoalexins, saponins, terpenoids, phenolics, alkaloids, etc., have been successfully tested as potential antibacterial agents. In this regard, alkaloids are a group of promising antibacterial agents, as they can be recovered from many sources and have a broad antibacterial spectrum with good activity against common clinical strains, including multidrug-resistant bacteria. Within this group, the isoquinoline alkaloids, those with an isoquinoline skeleton, have been very attractive to the scientific community and have therefore been extensively studied .…”
Section: Introductionmentioning
confidence: 99%